2022
DOI: 10.1002/cssc.202102262
|View full text |Cite
|
Sign up to set email alerts
|

Liquid‐ and Solid‐based Separations Employing Ionic Liquids for the Recovery of Platinum Group Metals Typically Encountered in Catalytic Converters: A Review

Abstract: The wide application range and ascending demand for platinum group metals combined with the progressive depletion of their natural resources renders their efficient recycling a very important and pressing matter. Primarily environmental considerations associated with state‐of‐the‐art recovery processes have shifted the focus of the scientific community toward the investigation of alternative recycling approaches. Within this context, ionic liquids have gained considerable attention in the last two decades chie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 233 publications
0
5
0
Order By: Relevance
“…Fe PGMs Fe PGMs PGMs slag Fe slag (13) Liu et al 43 and Trinh et al 44 clarified that γ PGMs-slag and γ Fe-slag were much higher than γ Fe-PGMs , and this result can also be explained by localized/delocalized electronics theory. Consequently, it can be found that Δσ Fe-PGMs < 0, μ PGMs Fe < μ PGMs slag , and ΔG T,P < 0 in the end.…”
Section: Formation Pathway and Mechanism Of The Fe-pgms Alloymentioning
confidence: 98%
See 1 more Smart Citation
“…Fe PGMs Fe PGMs PGMs slag Fe slag (13) Liu et al 43 and Trinh et al 44 clarified that γ PGMs-slag and γ Fe-slag were much higher than γ Fe-PGMs , and this result can also be explained by localized/delocalized electronics theory. Consequently, it can be found that Δσ Fe-PGMs < 0, μ PGMs Fe < μ PGMs slag , and ΔG T,P < 0 in the end.…”
Section: Formation Pathway and Mechanism Of The Fe-pgms Alloymentioning
confidence: 98%
“…In light of the recovery of valuable metals from secondary resources, pyro- and hydro-metallurgical technologies are currently mature in industrialization . The hydrometallurgical process usually faces a serious risk of secondary pollution of waste liquid, e.g., cyanide leaching, acid-oxidant leaching, chlorination leaching, etc., and increases the end-of-pipe cost. , In contrast, when it comes to recycling multiple secondary metal resources, the pyrometallurgical process has the superiority of high adaptability, large-scale application, and high recovery efficiency. , Pyrometallurgical technology includes smelting, pyrolysis, sintering, roasting, and vaporization, but herein, base-metal (Pb, Cu, Ni, and Fe) smelting collection is emerging and sophisticated in the development of spent PGM catalyst recovery .…”
Section: Introductionmentioning
confidence: 99%
“…Various mechanisms can be exploited relying on reactivity of specific PGM. Pd II can for example form an inner sphere complex with S-and N-based tethered ligands [86][87][88] or interact with ionic moieties [89,90] to remove it from other PGMs and/or base metals (entries 7-10) whereas different metal-trap interactions have to be exploited to efficiently remove both anionic and cationic Rh III aqua/chloride species from acidic aqueous solutions [91] (entry 11). Pt IV can be efficiently separated from Co II using ion exchange resins while processing the beforementioned proton exchange membrane fuel cells [92] (entry 12) while specific metal-metal interactions can be exploited to remove Pt II from other PGMs and base metals [93] (entry 13).…”
Section: Selective Trappingmentioning
confidence: 99%
“…Different physiochemical methods for PGM separation from the leaching solutions are described in the literature, such as solvent extraction (Costa et al 2013;Paiva et al 2022), ion exchange (Lanaridi et al 2022), molecular recognition technology (Izatt et al 2015) and molecular ion imprinted polymer (Limjuco and Burnea 2022). However, some of those techniques may have drawbacks such as inadequate metal recovery (especially for low concentrations of metals), high energy requirements, as well as high chemical costs and environmental problems.…”
Section: Introductionmentioning
confidence: 99%